Murine Type C viral envelope glycoprotein gp69/71 and lupus-like glomerulonephritis of New Zealand mice. An immunoperoxidase study. - Imamura, M. (1977)
The location of murine Type C viral envelope glycoprotein antigen in the glomerulonephritic kidneys of NZB and NZB/NZW F1 hybrid mice was analyzed by the indirect immunoperoxidase technique at light and electron microscopic levels. Immune complex deposits of the glycoprotein antigen were present in the glomeruli in mesangial and subepithelial sites. In addition to the glomerular depositions, viral envelope antigen was also present at the brush border of proximal tubular epithelial cells and in lymphoid cells infiltrating the kidneys of these mice.